Effects of ankle position during the Nordic Hamstring exercise on range of motion, heel contact force and hamstring muscle activation - Vicente-Mampel, J.; Bautista, I. J.; Martín, F.; Maroto-Izquierdo, S.; Van Hooren, B.; Baraja-Vegas, L. (Sports Biomechanics, 2022)
One of the main benefits of the Nordic Hamstring Exercise (NHE) is that it can be performed without the need of any extra material. However, numerous technical execution variables such as the ankle and pelvis position can influence the performance. The primary aims of this study were to investigate the effects of ankle position (i.e., plantar or dorsal flexion) on Nordic Hamstring Break Point (NHBP), repetition time and heel contact force. A secondary aim was to investigate differences in biceps femoris long head and semitendinosus muscle activation. Male professional field hockey players (n = 12) volunteered for the study. Paired t-tests were used to analyse the effect of ankle position on muscle NHBP, eccentric peak torque and repetition time. Ankle dorsal flexion resulted in a higher NHBP (p = 0.002, effect size [ES] = 1.48 [0.57 to 2.38]), repetition time (p = 0.004, ES = 0.98 [0.24 to 1.72]) and both absolute and relative heel contact force (p = 0.028, ES = 0.67 [0.01 to 1.34], p = 0.017, ES = 0.76 [0.07 to 1.44], respectively) compared to plantar flexion. Muscle activation was not significant different. This study showed a higher NHBP, absolute and relative heel contact force and repetition time with a dorsal flexed ankle vs. a plantar flexed ankle in the NHE, without changes in hamstrings muscle activation.